How to improve career construction for civil engineering students? - Ida Nugroho Saputro; Soenarto Soenarto; Herminarto Sofyan (Institute of Advanced Engineering and Science, 2023)
Career construction has received significant attention from Scholars in various countries. Strengthening career construction is believed to help individuals get closer to students’ career choices according to their field of expertise. However, studies on establishing career construction for vocational students involving instructional quality factors, social support, and career self-efficacy have not been found. Therefore, this study examines the antecedent factors that shape career construction by involving instructional quality, social support, and career self-efficacy of vocational high school students. This study proves that career construction is directly influenced positively by career self-efficacy. The instructional quality and social support, however, had no direct impact on how a profession was constructed. Another finding, career self-efficacy is directly influenced positively by the quality of instructional and social support of students. Finally, this study reveals that career self-efficacy acts as a mediator to mediate the effect of instructional quality and social support on the career construction of civil engineering vocational high school students. The findings of this study have significant ramifications for practitioners in vocational education who are creating strengthening programs or career development for vocational students.